2020
DOI: 10.1101/2020.07.08.179978
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The organizational principles of de-differentiated topographic maps in somatosensory cortex

Abstract: AbstractTopographic maps are a fundamental feature of cortex architecture in the mammalian brain. One common theory is that the de-differentiation of topographic maps links to impairments in everyday behavior due to less precise functional map readouts. Here, we tested this theory by characterizing de-differentiated topographic maps in primary somatosensory cortex (SI) of younger and older adults by means of ultra-high resolution functional magnetic resonance imaging together w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 115 publications
3
19
3
Order By: Relevance
“…Performing a task might increase integration between information from different fingertips. However, pRF width estimates in these two studies are much lower than those from two previous studies (Liu et al, 2021; Puckett et al, 2020) that reported fingertip pRF widths of ∼9-10 fingertips FWHM on average across S1. Since one study used passive stimulation (Puckett et al, 2020) and the other used an active task (Liu et al, 2021), task differences cannot account for these larger pRF width estimates.…”
Section: Discussioncontrasting
confidence: 87%
See 4 more Smart Citations
“…Performing a task might increase integration between information from different fingertips. However, pRF width estimates in these two studies are much lower than those from two previous studies (Liu et al, 2021; Puckett et al, 2020) that reported fingertip pRF widths of ∼9-10 fingertips FWHM on average across S1. Since one study used passive stimulation (Puckett et al, 2020) and the other used an active task (Liu et al, 2021), task differences cannot account for these larger pRF width estimates.…”
Section: Discussioncontrasting
confidence: 87%
“…However, pRF width estimates in these two studies are much lower than those from two previous studies (Liu et al, 2021; Puckett et al, 2020) that reported fingertip pRF widths of ∼9-10 fingertips FWHM on average across S1. Since one study used passive stimulation (Puckett et al, 2020) and the other used an active task (Liu et al, 2021), task differences cannot account for these larger pRF width estimates. Another possible explanation is that the two latter studies derived pRF parameters from phase-encoding stimulation sequences whereas both we and Schellekens et al (2021) used pseudo-random stimulation sequences that included periods without stimulation (better suited to estimate pRF width in regions with large receptive fields because they allow the BOLD response to return to baseline; Dumoulin and Wandell, 2008).…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations